The effects of construction on environmental resources in peninsular Malaysia: the perspective of land use planning - Asmawi, M. Zainora; Abdulaziz, Hassan; Ogundele, Ashim Oladimeji (2010)
Environment forms the basis upon which all human activities such as physical, social and economic take place. Malaysia is a nation that is blessed with the beauty of nature and at the same time advanced in terms of infrastructural development. Environmental resources are vital components of the environment that include land, vegetal resource, water bodies, atmosphere, flora and fauna. Nowadays, due to high rate of urbanization, rapid population and economic growth led to greater need of space for operation, which subsequently forced the construction industries to meet this demand. This gives rise to various forms of environmental degradations which lead to disruption of environmental equilibrium. The study assesses the effects of construction industries on the environment in the perspectives of land use planning. However, if proper measures are not taken, the consequences will never be of benefit to the country. Land use planning is an approach used to identify the relationship between construction activities and environmental resources. Generally, the study area covers Peninsula Malaysia because of the similarities of construction conditions and the environmental effects. The methodology employed in this study is based on the available data derived from the secondary sources of information. It also aims at suggesting ways of achieving sustainable construction activities so that our natural earth will not be harmed, destroyed or degraded.